Hubungan Praktik Kerja Industri dengan Kesiapan Kerja Siswa Program Keahlian Teknik Mesin di SMK Negeri 1 Sumatera Barat - Pratama, Wahyu; Erizon, Nelvi; Waskito, Waskito; Abadi, Zainal (Al-DYAS, 2024)
The problem in this study is the implementation of industrial work practices that have not been maximally implemented, this is evidenced by observations that it is found that students are not placed in accordance with their majors at school so that the implementation of industrial work practices does not run as it should and the learning and experience gained is not optimal. This study aims to measure how much relationship there is from industrial work practices with student work readiness. The research used is quantitative research which is correlational in nature where the sampling uses cluster random sampling technique with a total sample of 52 students consisting of 3 departments, namely Machining Engineering (TP), Welding Engineering (TLAS), Industrial Mechanical Engineering (TMI). The method used is associative quantitative research where data collection uses questionnaires and documentation. The results of this study indicate that there is a positive relationship between the value of industrial work practice (PRAKERIN) and student work readiness, which is 4.66% and the remaining 95.34% is related to other factors not examined. Thus this study shows that industrial work practices have an influence on students' work readiness to enter the industrial world. This is evidenced by the research results which have a positive value.